Bioantifungal activity of selected medicinal plants extracts against roots rot of fungal disease - Zahari, Rozihawati; Halimoon, Normala; Sajap, Ahmad Said; Ahmad, Mohd Farid; Mohamad Kasim, Mohamad Roslan (Science Publishing Group, 2014)
Root rot disease of fungal such as Ganoderma philippii, Phellinus noxius and Rigidoporus microporus are well known destructive fungus to plant root. The in vitro antifungal screening of selected medicinal plants was studied against the disease. The twelve of Malaysian medicinal plants including the leaves of Aglaia argentea, A. leucophylla, A. grandis, A. odorata, A. odoratissima, A. varrisquama, Alium sativum (bulbs) and Cassia alata, Catharanthus roseus stems and leaves, Derris elliptica leaves and Tinospora baenzigeri stems were extracted using different types of solvents extraction i.e, dichloromethane (DCM), acetone and methanol at the concentration of 20 mg/mL. The extracts were studied for antifungal activities against three species of fungal disease including G. Philippii, P. noxius and R. microporus. The antifungal activities of the extracts were determined by the presence or absence of fungal inhibition zone growth on Potato dextrose agar (PDA). The extracts shows a significant results but varying in their antifungal activities on the selected fungal. The DCM and acetone extracts of C. roseus stems had the highest antifungal activities against R. microporus fungus compared to methanolic extract. On the other hand, acetone extracts of A. argentea leaves also gave the highest antifungal activities against G. philippii compared to other extracts. However, all of the extracts didn’t show any inhibition zone on P. noxius culture. In general, the DCM extracts of C. roseus stems contain the most of bio-antifungal of active compounds against R. microporus of fungal disease.